Piekielne figle mego kija… Rozrywkowy rekwizyt w opowiadaniu Pan Wesołowski i jego kij Bolesława Prusa - Zalewski, Cezary (Przestrzenie Teorii, 2025)
The article analyses the function performed by a prop (specifically a man’s cane) in Bolesław Prus’s story. The analysis leads to the conclusion that the prop is an unrecognizable substitute for a person. It plays the role of a so-called double authority: it is what the owner would like to be and sets new objects of desire for him.